PEMANFAATAN LAHAN PERKARANGAN SEBAGAI ALTERNATIF PENDAPATAN PETANI (STUDI KASUS USAHATANI LAHAN PERKARANGAN DI KECAMATAN BLANGBINTANG - Rhafiri Rahman; Zulkifli Zulkifli (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This research purposes to knowing the contribution of land utilization of yard to the income of landowners in Blang Bintang Sub-district, Aceh Besar.The using model of this research is qualitative then described descriptively, with using primary data through observing and interview (face to face). While quantitative analysis is described based on the results of questionnaires that have been distributed to respondents in Blang Bintang sub-district. This research was conducted at Blang Bintang Sub-district, where sample were taken from several villages that were still actively utilizing farming business activities on land of yard with 30 respondents and not all villages have respondents who carry out optimization of the use of the land area. The result of this research presented that all samples from the entire population have used the land as an alternative income for farmers in Blang Bintang Sub-district, Aceh Besar. In addition, farming business in the yard also experience a change in income budget that increases after the land is used for farming business, the increase in income of each respondent was Rp 2.104.350. Benefits from land of yard not only provide additional household income, but can also save on family consumption expenses.Keyword:Farming Business, Land Utilization of Yard, Income